ANALYSIS OF FINANCING MODELS IN THE NEW NORMAL ERA (CASE STUDY OF ISLAMIC BANKS) - Deery Anzar Susanti (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to determine how Islamic financial institutions channel their fundsto society in thenew normal era.One of the functions of Islamic financial institutions is to channel funds to the public.During the spread of the Covid 19 virus, the process of channeling funds was carried out by Islamic financial institutionsof course it has high barriers, when the economy is currently experiencing a significant decline.This can be seen from the number of people affected by layoffs, not only that, the people's purchasing power during the spread of Covid 19 also decreased.Therefore, here the researcher wants to do research on the models used by financial institutions in channeling funds.This type of research is descriptive qualitative research, where the researcher will describe the phenomena that occur in the field.Keywords: Financing, Islamic Financial Institutions, New Normal